How social-ecological systems resilience unfolds from distinct worldviews - Oliveira, Bruno M.; Boumans, Roelof; Fath, Brian D.; Harari, Joseph (Frontiers in Sustainable Resource Management, 2024)
Resilience is a critically important factor to consider for sustainably managing natural resources and social-ecological systems (SESs). Each social system will, collectively, have its own goals for how resources are perceived and the principles that underpin their resilience, and, multiple actors, individually, will approach the question with different perspectives. Here, we represent these plural perspectives in terms of worldviews, using the typologies from cultural theory. We combined the underpinning resilience principles from a previously built SES model to assess the extent to which these worldviews influence the results. Resilience was measured using a prototype Dynamic Resilience Index (DRI) validated in a previous publication. The results show the resilience of our SESs will behave in three different ways depending on each worldview used. Free markets (individualists) start the simulation period with a higher resilience. Strong governance (hierarchy) will take a higher position around 2025 and maintain the best value to the end of the simulation in 2100. The precautionary principle (egalitarians) starts with the lowest values for the DRI but ends closer to the strong governance, and it is the only worldview that increased its resilience throughout the simulation. Each worldview couples better to a particular management approach, and the SES behavior responds accordingly. The relevance for the governance of the SES is great as each worldview brings flawed contributions to resilience and wellbeing. Our research also shows that a possible negotiated solution between these worldviews would locate resilience inside the “solution space,” which is graphically determined and discussed. Adopting each worldview is then discussed in terms of contributions and problems they imply to the system's resilience.